Learning consumption: Media, literacy, and the legacy of One Laptop per Child. Issue 2 (14th March 2016) - Ames, Morgan G.
ABSTRACT: This article examines one of the largest interventions in computer-based learning currently underway, the One Laptop per Child (OLPC) project, with 2.5 million laptops in use worldwide. Drawing on 2010 and 2013 fieldwork investigating a project in Paraguay with 10, 000 of OLPC's "XO" laptops, I explore the ways in which participants interpreted leisure laptop use as "learning." I show that the most captivating uses of the laptops were not "productive" or programming-centric, as OLPC's developers hoped, but "consumptive" and media-centric, focused on music, videos, and video games. I discuss the learning benefits and drawbacks of this use, as understood by participants and in light of education research, and in light of the broader context of transnational corporations interested in marketing to these children. In the process, I weigh OLPC's utopian dreams against the interests of the child beneficiaries, concerns of media imperialism, and a potential shift in the meaning of computers.